2024
DOI: 10.1007/s10648-024-09864-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Problem-Based, Project-Based, and Case-Based Learning on Students’ Motivation: a Meta-Analysis

Lisette Wijnia,
Gera Noordzij,
Lidia R. Arends
et al.

Abstract: In this meta-analysis, we examined the effects on students’ motivation of student-centered, problem-driven learning methods compared to teacher-centered/lecture-based learning. Specifically, we considered problem-based (PBL), project-based (PjBL), and case-based learning (CBL). We viewed motivation as a multifaceted construct consisting of students’ beliefs (competence and control beliefs), perceptions of task value (interest and importance), and reasons for engaging in tasks (intrinsic or extrinsic). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…Rooted in constructivist learning theories, PjBL shifts the focus from traditional teacher-led instruction to student-centered inquiry and collaboration, where students engage in authentic, real-world projects to construct knowledge and solve complex problems Singgih Subiyantoro / Exploring Teachers' Perspectives on their Role in Facilitating Project-Based Learning: A Comparative Study of Elementary, Middle, and High School (Chang et al, 2024;Melia Astiana, Maya Malinda, Anny Nurbasari, 2021;Şahin & Kılıç, 2024). Over the years, PjBL has garnered attention from educators, researchers, and policymakers for its potential to promote critical thinking, creativity, communication, and collaboration skills, which are essential for success in the modern workforce (Hao et al, 2024;Şahin & Kılıç, 2024;Wijnia et al, 2024). Despite the growing interest and adoption of PjBL in educational practice, there remains a gap in understanding the intricate role of teachers in facilitating this instructional approach.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rooted in constructivist learning theories, PjBL shifts the focus from traditional teacher-led instruction to student-centered inquiry and collaboration, where students engage in authentic, real-world projects to construct knowledge and solve complex problems Singgih Subiyantoro / Exploring Teachers' Perspectives on their Role in Facilitating Project-Based Learning: A Comparative Study of Elementary, Middle, and High School (Chang et al, 2024;Melia Astiana, Maya Malinda, Anny Nurbasari, 2021;Şahin & Kılıç, 2024). Over the years, PjBL has garnered attention from educators, researchers, and policymakers for its potential to promote critical thinking, creativity, communication, and collaboration skills, which are essential for success in the modern workforce (Hao et al, 2024;Şahin & Kılıç, 2024;Wijnia et al, 2024). Despite the growing interest and adoption of PjBL in educational practice, there remains a gap in understanding the intricate role of teachers in facilitating this instructional approach.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that students engaged in PjBL projects demonstrate improved academic performance, higher motivation, and enhanced problem-solving skills than those in traditional classrooms (Abuhmaid et al, 2020;Cai et al, 2023;Zhang et al, 2024). Furthermore, research has identified various models and frameworks for designing and implementing PjBL, such as the Buck Institute for Education's (BIE) Gold Standard PBL model and the framework proposed by Thomas in Wijnia (Wijnia et al, 2024). These models emphasize essential elements of effective PjBL, including authentic challenges, student autonomy, inquiry and investigation, and public presentation of learning outcomes (do Amaral et al, 2023;Suartama et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations